Air quality impact of intelligent transportation system actions used in a decision support system for adaptive traffic management. (2015) - Vranckx, Stijn; Lefebvre, Wouter; Poppel, Martine Van; Beckx, Carolien; Theunis, Jan; Mascia, Margherita; Hu, Simon; Köbl, Robert; Litzenberger, Martin
The presented traffic control system (CARBOTRAF) combines real-time monitoring of traffic and air pollution with simulation models for traffic, emission and local air quality predictions to deliver on-line recommendations for alternative adaptive traffic management. The aim of introducing a CARBOTRAF system is to reduce BC and CO2 emissions and improve air quality by optimising the traffic flows. A chain of models combines microscopic traffic simulations, emission models and air quality simulations for a range of traffic demand levels and intelligent transport system (ITS) actions. These ITS scenarios simulate combinations of traffic signal optimisation plans and variable messaging systems. The real-time decision support system uses these simulations to select the best traffic management in terms of traffic and air quality. In this paper the modelled effects of ITS measures on air quality are analysed with a focus on BC for urban areas in two European cities, Graz and Glasgow.